The properties of Mrs. Micaela Villegas Hurtado de Mendoza, “La Perricholi” - Brito Ramos, Juan José (2025)
This article investigates the real estate properties acquired by Micaela Villegas, “La Perricholi”, a singer and theater actress from Lima of the second half of the 18th century, whose career continued as a theater entrepreneur in the early years of the 19th century. Known in the colonial society of Lima at the time for being the lover of Viceroy Manuel de Amat y Junyent, who governed Peru between 1761 and 1776, however, serious research reveals that Micaela Villegas, overcoming the prejudices related to her occupation and the difficulties of a woman in a patriarchal and conservative society, knew how to properly manage her income —her work product—, which allowed her to acquire various properties in the city of Lima.